2018
DOI: 10.1021/acssensors.8b00709
|View full text |Cite
|
Sign up to set email alerts
|

Diaminocyclohexane-Functionalized/Thioglycolic Acid-Modified Gold Nanoparticle-Based Colorimetric Sensing of Trinitrotoluene and Tetryl

Abstract: Detection of explosive residues in soil and postblast debris is an important issue in sensor design for environmental and criminological purposes. An easy-to-use and low-cost gold nanoparticle (AuNP)-based colorimetric sensor was developed for the determination of nitroaromatic explosives, i.e., trinitrotoluene (TNT) and tetryl, capable of analyte detection at picomolar (pM) levels. The sensor nanoparticles were synthesized by functionalizing the negatively charged thioglycolic acid (TGA)-modified AuNPs with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…To that end, quantum dots [65,66], plasmonic nanoparticles [67][68][69][70], carbon nanotubes [71] and graphene [72] have been widely explored for the development of affinity-based nanoprobes to detect common narcotics [65,66], anabolic steroids [71], drugs with abuse potential [69], explosives [67,72] and pathogens that can potentially be linked to bioterrorism [68], as well as to determine time since death [70]. Moreover, wearable biosensors can monitor continuously and in real time adverse lifestyle habits associated with criminal behaviour, such as the excessive use of alcohol [73].…”
Section: Molecular Sensingmentioning
confidence: 99%
“…To that end, quantum dots [65,66], plasmonic nanoparticles [67][68][69][70], carbon nanotubes [71] and graphene [72] have been widely explored for the development of affinity-based nanoprobes to detect common narcotics [65,66], anabolic steroids [71], drugs with abuse potential [69], explosives [67,72] and pathogens that can potentially be linked to bioterrorism [68], as well as to determine time since death [70]. Moreover, wearable biosensors can monitor continuously and in real time adverse lifestyle habits associated with criminal behaviour, such as the excessive use of alcohol [73].…”
Section: Molecular Sensingmentioning
confidence: 99%
“…In addition to sizes and shapes of AuNPs, many studies have shown that the surface charge of AuNPs played a critical role in modulating cellular uptake [134]. The surface charge of AuNPs includes positively charges [135], negatively charges [136] and neutral charges [137]. Positively charged surfaces preferentially increase cellular uptake due to the negatively charged surface of the cells.…”
Section: Surface Chargementioning
confidence: 99%
“…The excessive use of nitro compounds to fulfill human requirements leads to an increase in the concentration of aforesaid pollutants in the atmosphere and causes different forms of environmental pollution including water pollution. 5 Also, the recent literature supported the contamination of groundwater and other water bodies by explosive materials like TNT 5–9 and their derivatives. The contamination of water systems by these explosive materials makes them highly toxic and that's why the US Environmental Protection Agency (EPA) has set a permissible limit of 2 ppb in drinking water.…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, we need very sensitive, selective and cost-effective methods for the detection of nitro compounds at low concentrations. Various techniques are available in the literature for the detection of explosive compounds such as surface plasmon resonance; RDX, 12 colorimetric; TNT, Tetryl, 13 electrochemical; 14 liquid chromatography-mass spectrometry, 15 fluorometry (TNT) 16 and surface-enhanced Raman scattering; (TNT), 17 high-performance liquid chromatography; (TNT, RDX, PETN & HMX), 18,19 etc. Among these reported methods, fluorescence-based detection of explosive compounds is generally preferred due to its quick response, cost-effectiveness, short duration, high selectivity, and easy operation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation